What makes muslim tourists loyal to halal destinations in yogyakarta? a loyalty analysis using the SEM Method - Pratiwi, Heni (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
This study aims to analyse the relationship among halal image, halal quality, halal value, halal attributes satisfaction toward overall satisfaction and loyalty in halal tourism issues. This type of research is quantitative research which used primary data (questionnaire) obtained through 200 respondents who have travelled halal destination in Daerah Istimewa Yogyakarta, the analysis in this study used the Structural Equation Modelling method with Lisrer 8.80 software. The respondents should choose one of ten halal destination’s categories which has been specified on the questionnaire. In this study, we examine the determinants of tourist overall satisfaction and loyalty. The findings confirm that halal value and halal attribute satisfaction contribute to generating tourist on overall satisfaction. The results also show that only overall satisfaction has significant and positive effect directly enhance tourist loyalty. this study offers the novelty on the explanation of the opportunities and challenges in developing and marketing halal tourism through tourist loyalty.